Theoretical and Experimental Study on Rapid Decompression Oscillation in Altitude Chamber - Zifeng Tian; Jianfeng Lu; Zhao Gu; Lihua Yu; Hao Zhou; Lijun Yang (International Journal of Aerospace Engineering)
Given the frequent airflow excitation phenomenon caused by the rapid decompression of the altitude chamber, the mathematical model of the nonlinear system of the rapid decompression of the altitude chamber is established. The polynomial parameter method is used to evaluate the characteristics of airflow oscillation, and a rapid decompression test system is built. The test results verify the pressure oscillation phenomenon of the numerical simulation. This paper proves the phenomenon of fluid-induced vibration in the process of rapid decompression and determines that the main factors affecting the induced oscillation are the diameter of the pipe (throat), pressure difference between the two chambers, and initial pressure conditions. Specifically, this study establishes safety and reliability for preventing engineering accidents caused by resonance in the altitude chamber.